Analysis of Argument-Driven Inquiry Activity in Chemistry Textbooks - Iis Intan Widiyowati; Ainun Rezkiva Arif; Sukemi Sukemi (Jurnal Tadris Kimiya, 2023)
Argument-Driven Inquiry (ADI) in science learning can improve students' argumentation skills and understanding of concepts. In the textbooks, it is important to have ADI activities inside. This research aims to analyze ADI activities in the high school chemistry textbook Revised Curriculum 2013. This research used nine indicators of ADI activities: questions, evidence, student explanation, scientific theories, argumentation, communication and justification, analysis, connection, investigation report, and reflection. The research method used a descriptive instrument as an analysis sheet prepared based on ADI activities. Data was collected using documentation techniques and data analysis using content analysis of ADI activities. The results showed that the reliability test of the data obtained was 0.94 in the very good category. The ADI activity most found in textbooks is evidence activity, with a percentage of 31.25 Meanwhile, the textbook needs to explain question and answer and reflection activities. The textbook needs to increase ADI activities that support student-centered learning and teaching.